Hamas dan Fatah: Tekanan Ideologi dalam Membebaskan Palestina - Rahman, Badra Jultouriq (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2020)
Hamas and Fatah are the two dominant Palestinian political parties that have the same goal of freeing Palestinians from Israeli occupation. But there are ideological differences between Hamas and Fatah, Fatah with secular nationalist ideology while Hamas with Islamic ideology. The difference in ideology is considered to be the cause of the lack of cooperation between the two to free Palestine from Israeli occupation. This paper seeks to answer the question of why Hamas and Fatah did not unite to free Palestine from Israeli occupation when both have the same goal, whether differences in ideology are the main obstacle for Hamas and Fatah not to unite to liberate Palestine. In this paper the authors use the theory of conflict resolution and descriptive methods. The results of this study indicate that ideology is indeed one of the reasons Hamas and Fatah are not cooperating, because these two ideologies are in conflict with each other, but the historical conflict factor between Hamas's predecessors, the Muslim Brotherhood and Fatah has affected the inability of Hamas and Fatah to cooperate in efforts to liberate Palestine because differences of opinion in addressing resistance to Israel, then coupled with the disappointment of Hamas against Fatah which was hit by the issue of corruption and abuse of power, and Hamas considers Fatah to recognize the existence of Israel after signing the Oslo Declaration. Furthermore, it is hoped that this article can be used as a reference and comparison material for similar research.